On the performance of tests for the detection of signatures of selection : a case study with the Spanish autochthonous beef cattle populations - González Rodríguez, Aldemar (2016)
Fil: González Rodríguez, Aldemar. Universidad de Zaragoza. Departamento de Anatomía, Embriología y Genética. Saragossa, España.